Rol del cuidador en niños con parálisis cerebral. - Colcha Llamuca, Erika Maribel (2024)
Infantile cerebral palsy (ICP) is a set of permanent, non-progressive disorders that affect movement, posture, and neurodevelopment of the fetal or infant brain, causing multiple limitations in the child. Children with ICH may have different needs, from mild to severe, and require different care areas. The primary caregiver is a person who voluntarily or indirectly assumes responsibility for the child's care. The child's disability may affect his or her mother's ability to support the child, leaving the child in the care of another person. The primary caregiver's role is to provide a wide range of care, such as nutrition, mobility, personal hygiene, seizure control, and transportation to medical appointments. They must have the appropriate knowledge and skills to meet the child's needs, including motor skills of sucking, chewing, and swallowing, as well as adequate nutrition and hydration. The role of the caregiver is to supervise and facilitate the development of physical, cognitive, emotional, mental, and social skills. They also participate actively in various activities, such as feeding, dressing, and daily care. The present study aims to determine the role of the caregiver in patients with CLI, which was developed with a literature review in databases such as Google Scholar, SciELO, PubMed, Medline, Dialnet, and Redalyc. Focused on nursing professionals and caregivers of children with this pathology to reinforce knowledge about care, prevent complications, stimulate the child's cognitive, motor, and social potential to the maximum, and the key points to consider about the appropriate management options in the activities of daily living.